The COVID-19 Assessment for Survival at Admission (CASA) Index: A 12 Months Observational Study - Bagnato, Gianluca; La Rosa, Daniela; Ioppolo, Carmelo; De Gaetano, Alberta; Chiappalone, Marianna; Zirilli, Natalia; Viapiana, Valeria; Tringali, Maria Concetta; Tomeo, Simona; Aragona, Caterina Oriana; Napoli, Francesca; Lillo, Sara; et al. (Frontiers in Medicine, 2021)
Objective: Coronavirus disease 2019 (COVID-19) is a disease with a high rate of progression to critical illness. However, the stratification of patients at risk of mortality is not well defined. In this study, we aimed to define a mortality risk index to allocate patients to the appropriate intensity of care. Methods: This is a 12 months observational longitudinal study designed to develop and validate a pragmatic mortality risk score to stratify COVID-19 patients aged ≥18 years and admitted to hospital between March 2020 and March 2021. Main outcome was in-hospital mortality. Results: 244 patients were included in the study (mortality rate 29.9%). The Covid-19 Assessment for Survival at Admission (CASA) index included seven variables readily available at admission: respiratory rate, troponin, albumin, CKD-EPI, white blood cell count, D-dimer, Pa02/Fi02. The CASA index showed high discrimination for mortality with an AUC of 0.91 (sensitivity 98.6%; specificity 69%) and a better performance compared to SOFA (AUC= 0.76), age (AUC= 0.76) and 4C mortality (AUC= 0.82). The cut-off identified (11.994) for CASA index showed a negative predictive value of 99.16% and a positive predictive value of 57.58%. Conclusions: A quick and readily available index has been identified to help clinicians stratify COVID-19 patients according to the appropriate intensity of care and minimize hospital admission to patients at high risk of mortality.